Protective role of progesterone on lung injury induced by ischemia reperfusion of the lower limbs - AK, ESİN; OKTAY, NİHAL ŞEHKAR; ÖZBEYLİ, DİLEK; AK, KORAY (My University, 2022)
Objective: Remote lung injury is one of the most challenging issues in patients undergoing ischemia reperfusion (IR) injury of the lower limbs. We examined the role of progesterone (PG) on the remote injury of the lungs seen after IR of the lower limbs. Methods: Eighteen male Sprague Dawley rats were divided into three groups. (1) Control: rats had only two physiological saline injections intraperitoneally (i.p.) 2 h apart under general anesthesia. (2) IR: underwent 2 h tourniquet induced ischemia for both lower limbs followed by 2 h of reperfusion. Animals were injected with physiological saline (i.p.) before both ischemia and reperfusion. (3) IR + PG: rats underwent the same IR protocol as the IR group and were injected with PG (16 mg/kg, i.p.) before both ischemia and reperfusion. After reperfusion, rats were sacrificed, and lung tissues were taken out for histopathologic and biochemical analyses. Results: In IR + PG group, tissue levels of malondialdehyde and nitric oxide decreased significantly compared with the IR group (p<0.01). Similarly, glutathione level and superoxide dismutase and glutathione S-transferase activities significantly increased in the IR + PG group than in the IR group (p<0.05, p<0.01, and p<0.05, respectively). In light microscopy, reduced inflammatory cell infiltration, amelioration in alveolar structure, and mild vascular congestion in the parenchyma were seen in the IR + PG group. A significant improvement in histopathologic score was seen in the IR + PG group compared with the IR group (p<0.001). Conclusion: PG might be effective in attenuating remote injury of the lung in lower body IR via its antioxidant function
Keywords: schemia; lower limb; lung; remote organ injury; reperfusion